Rationalizing poverty in New York: Tales from the middle class - Ali, S; Ohls, C; Parker, G; Walker, R (Routledge, 2018)
Although poverty rates in the US are among the highest in the OECD (Organization for Economic Co-operation and Development), there is limited public support for a new war on poverty and persistent opposition of the provision of generous welfare. This article addresses the long-standing puzzle of why such attitudes have proved so resistant to change. Based on focus groups discussions, this article offers the suggestion that this resistance may be due to public attachment to a shared conceptual model of poverty. The model embraces the American dream and a belief that opportunity enables anybody with adequate effort to achieve all their aspirations.